Variable frequencies of peripheral T-lymphocyte subsets in the diabetes spectrum from type 1 diabetes through latent autoimmune diabetes in adults (LADA) to type 2 diabetes - Tan, Tingting; Xiang, Yufei; Deng, Chao; Cao, Chuqing; Ren, Zhihui; Huang, Gan; Zhou, Zhiguang (Frontiers in Immunology, 2022)
T lymphocytes are key players in the pathogenesis of autoimmune diabetes. We recruited subjects with T1D (n=81), LADA (n=82), T2D (n=95) and NGT (n=218) and analyzed the percentages of T-lymphocyte subsets, including T helper 1 (Th1), T helper 2 (Th2), T helper 17 (Th17), T cytotoxic 1 (Tc1), regulatory T cells (Tregs), effector T (Teff), naïve T, central memory T (Tcm), and effector memory T (Tem) cells by flow cytometry. LADA patients possessed similar frequencies of IFN-γ+CD4+ T (Th1), IFN-γ+CD8+ T and CD4+ Teff cells compared with T1D patients, but much lower than those of NGT subjects. Like T2D patients, LADA patients had increased frequencies of CD4+ Tem and CD8+ Tem cells with respect to T1D and NGT subjects. In LADA patients, Th2 cells were decreased while CD4+ Tcm cells were increased compared with NGT subjects. Notably, we observed significant negative correlations between the CD4+ Tcm cell frequency and C-peptide in LADA subjects. These data demonstrates that LADA patients possess T-cell subset changes resembling both T1D and T2D and represent the middle of the diabetes spectrum between T1D and T2D. Based on these T-cell subset alterations, we speculate that autoimmunity-induced β-cell destruction and inflammation-induced insulin resistance might both be involved in the pathogenesis of LADA.